Efficiency of Using PERI Formwork in Low-Rise Buildings Project - Monika Natalia; Hendra Alexander; Merley Misriani; Muhammad Zaqharia; Dani Kurniawan (Kadiri University, 2023)
Concrete construction is still the main choice because of its high strength, durability, and ability to withstand heavy loads. In reinforced concrete construction, formwork is a fairly important element. Formwork significantly impacts the efficiency of construction implementation. Formwork innovation has found PERI formwork to be a solution that many consider more efficient. Efficient use of PERI formwork is an important focus to increase productivity, minimize time, and reduce construction costs. This research aims to analyze the quality, cost, and implementation time of PERI formwork compared to conventional formwork in 2-story buildings. Quantitative methods are used to evaluate quality (strength of bending, safe deflection, and strength of the shear) using SAP 2000, implementation time using Microsoft Project, and project costs using unit price analysis. The research results show that using the PERI formwork system can provide various efficiencies in formwork work. PERI formwork has been proven stronger in withstanding loads and meets current load regulations. It can save project implementation time by up to 21 working days (24.7%) with a cost reduction of 4.72%. This is because the installation cycle is faster, which can increase productivity and reduce costs. So, using the PERI system formwork has proven efficient and can be the best choice for low-rise building construction projects.